BS EN IEC 61347-2-12. Lamp controlgear. Part 2-12. Particular requirements for d.c. or a.c. supplied electronic controlgear for discharge lamps (excluding fluorescent lamps) (17th July 2020) - British Standards Institution,
No abstract available